Symposium 7: New Directions in Research into Learning Cultures in Online Education - Goodfellow, Robin (Proceedings of the International Conference on Networked Learning, 2008)
This paper introduces the theme of culture in online learning and a forthcoming edited collection of research that addresses the theme of ’learning cultures in online education’, to be published by Continuum books later this year (Goodfellow & Lamy in preparation). It argues that research on online learning cultures is an important corollary to the use of e-learning to develop ’transnational’ and ’cross-border’ education markets if the social and pedagogical benefits from these developments are to keep pace with the corporate and institutional ones, but that it is also a corollary to the teaching of the increasingly diverse learner cohorts that inhabit formal online learning communities, and to the increasingly blurred distinction between these learning communities and the more informal ones that are appearing in a variety of sites of online social networking. Some of the research into online learning cultures to date is reviewed, and broadly characterised as motivated by either: i) a concern with the influence on international learners’ individual and group identity of prevalent ’western’ approaches to online education (social constructivism, techno-rationalism), and the English language; ii) a desire to understand the ways that online learning is played out through language, where the presentation and disclosure of identities by learners is inflected by their own cultural backgrounds and/or by the reduced cues of the electronic medium, which hide indicators such as accents, appearance, age, gender etc.; or iii) an interest in the emergence of ’new’ cultural and social identities in virtual learning communities which draw on contemporary cybercultures of the internet, as well as systems of cultural relations inherited from conventional educational or corporate settings. Some of the new approaches to issues of culture in online education taken by the contributors to the book are then discussed. These include the contribution of Charles Ess, addressing the continuing relevance of a conceptualisation of culture that equates it with national identity and locates it in the behaviour of individual learners; Charlotte Gunawardena’s work on the processes through which identities and value systems are negotiated amongst actors in virtual environments; and Jay Lemke’s and Caspar van Helden’s discussion of the relationship between formal educational and popular media cultures. The two other papers which comprise this symposium are briefly introduced, being Leah Macfadyen’s account of the role of ritualised and textualised language in the construction and presentation of identities online, and Anne Hewling’s discussion of the influence of the ’behaviour’ of technical environments on the cultural ecology of online learning communities. Two directions for future research are proposed. One involves switching attention away from the generalisations about the behaviour characteristics of local consumers of global online learning products, and turning it on to their possibilities for re-purposing these products. The other involves the investigation of learners’ uses of the social web and the attitudes to learning that this is becoming associated with.